The Impact of Hybrid Learning Media: Laskar Pelangi Film in Cultivating Patriotism and Identity - Farid, Akbar; Indrayati, Tri; Rotari, Septi (Journal of Education and Teaching Learning, 2025)
Patriotic attitudes are attitudes that must be instilled in every Indonesian citizen. This research aims to describes the influence of film media on patriotic attitudes as identity formation in students after the Covid-19 pandemic. This study uses a quantitative approach using a descriptive research method. The primary data source is students of German Language Education, Yogyakarta State University. The data collection technique used is a questionnaire regarding the influence of the Laskar Pelangi Film media on the attitude of patriotism as a student's self-identity which is given through a google form. Data analysis used in this study is an independent sample t-test with the help of SPSS 22.0. The results of the independent sample t-test analysis show a sig. value (2-tailed) of 0.030 <? 0.05, so Ho is rejected and Ha is accepted. There is a significant difference in the patriotic attitudes of students before and after using the Laskar Pelangi Film media as identity formation in the Pancasila Education course.